2016
DOI: 10.1016/j.joca.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of synovitis in osteoarthritic knees and its association with clinical features

Abstract: In individual patients synovitis fluctuates during disease course. Synovitis change was not associated with change in pain. Increase in synovitis is associated with cartilage deterioration, suggesting a role for synovitis as a target for disease-modifying treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 32 publications
4
29
0
1
Order By: Relevance
“…However statistical significance was only reached for BML worsening in the medial PFJ. On the other hand, we found statistically significant associations between Hoffa-synovitis and widespread structural damage both cross-sectionally and longitudinally, which is in line with previous publications 912 . To the best of our knowledge this is the first large scale epidemiologic study to report the prevalence of SHFP hyperintensity and its relation to the presence of site-specific structural damage in the knee.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However statistical significance was only reached for BML worsening in the medial PFJ. On the other hand, we found statistically significant associations between Hoffa-synovitis and widespread structural damage both cross-sectionally and longitudinally, which is in line with previous publications 912 . To the best of our knowledge this is the first large scale epidemiologic study to report the prevalence of SHFP hyperintensity and its relation to the presence of site-specific structural damage in the knee.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, we recently reported in a longitudinal study that knees that develop both PFJ and TFJ structural damage after 7 years of follow-up often start with isolated PFJ involvement at baseline 32 . In a similar fashion to Hoffa-synovitis, which is a recognized surrogate of widespread cartilage damage 9,11,12 , SHFP hyperintensity may potentially represent a site-specific surrogate of cartilage damage earlier in the disease process.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, other studies, using imaging modalities for synovitis assessment, have shown associations between inflammation and clinical outcomes 7,11 . Furthermore, synovitis is known to fluctuate, and this fluctuation has shown correlations to fluctuations in clinical outcomes 25,26 , although conflicting evidence exists 27,28 . The discrepancy with our results may be caused by the fact that inflammation was only assessed once, while clinical aspects were assessed multiple times during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its relationship with knee pain, synovitis is also strongly associated with more rapid progression of cartilage loss in OA joints and initiation of cartilage loss in joints without OA [7][8][9][10]. This suggests that synovial inflammation can occur upstream of cartilage erosive mechanisms and could therefore not only be a therapeutically accessible symptom-but also diseasemodifying target.…”
Section: Introductionmentioning
confidence: 99%